Dysfunctional Attitudes Mediate the Relationship Between Childhood Emotional Neglect and Anhedonia in Young Adult Major Depression Patients - Wang, Peilin; Zhang, Nan; Ma, Simeng; Kang, Lijun; Wang, Wei; Zong, Xiaofen; Bai, Hanping; Li, Ruiting; Liu, Zhongchun (Frontiers in Psychiatry, 2022)
Background: Childhood traumas are well-established risk factors for major depressive disorder (MDD). However, the relationship between childhood traumas types and MDD symptoms is unclear. The present study tested the hypothesis that childhood traumas affect specific types of anhedonia in depression and the mediating role of dysfunctional attitude. Methods: Within this cross-sectional study, 310 young adult patients with MDD completed the PHQ-9, CTQ-SF, DAS, and SHAPS. The statistical analyses used the Mann-Whitney U test, Spearman's rank correlation, and multiple regression analysis. Mediation analyses were tested by the structural equation model (SEM). Results: Spearman's rank correlation analysis showed positive correlations between the SHAPS, CTQ-SF, and DAS total score (p < 0.05). The EA, EN, PN, and SHAPS scores were positively correlated (p < 0.05). Among the four factors of anhedonia, social interaction and interest/pastimes were positively correlated with EA, EN, and PN (p < 0.05), the sensory experience was positively correlated with EN (p < 0.01), and diet did not correlate with childhood traumas. Stepwise regression analysis showed that dysfunctional attitude and emotional neglect were the main influencing factors of sensory experience (p < 0.001) and social interaction (p < 0.001). Dysfunctional attitude and physical neglect were the main factors influencing interest/pastimes (p < 0.001). SEM analysis found that dysfunctional mediated between childhood traumas and anhedonia. Conclusions: The degree of anhedonia was related to dysfunctional attitudes and childhood traumas. The childhood emotional neglect experience was the most important and was related to sensory and social anhedonia. Dysfunctional attitudes played a mediating role between childhood neglect and anhedonia. Early psychotherapy targeting young adult MDD patients with childhood emotional neglect may help decrease symptoms of anhedonia.